Peran Pelatihan Kewirausahaan dan Minat Siswa Yayasan Tahfidzul Ar-Rahmani Tangerang Selatan - Lies Sunarmintyastuti; Hanggono Arie Prabowo; Dwi Narsih; Hugo Aries Suprapto; Dellia Milla Vernia (Jurnal Ilmiah Wahana Pendidikan, 2021)
Entrepreneurship is an activity that can provide independence to students. Teachers and parents, can contribute to the maximum, if between parents and teachers can work well together. But there are still many schools that have not given a large portion of the value of entrepreneurship, while entrepreneurship is very important in developing students to improve economic and social independence. The purpose of this study is to describe the role of entrepreneurial training and student interest in the Tangerang Arrahmani Foundation. This study used descriptive qualitative method. The population was 30 students, and the sample was 10 students. The sampling method uses a purposive sample method. The results of the study produced the role of entrepreneurship training and interest in supporting entrepreneurship. Teachers can help in school with the training that has been given. While parents can help familiarize training at home.